(untitled) (International Association of Biologicals and Computational Digest, 2022)
Forest changes are now being rapid because of the higher rate of climatic variability. Landscape-scale evaluations of forest productivity are important to understand the response of forest species to changing climate. Net primary productivity (NPP) changes over long-term (from the year 1981 through 2006) was studied in the forest ecosystems of Gujarat state, India. The NPP product used in the study is derived from National Oceanic and Atmospheric Administration’s Advanced Very High Resolution Radiometer scanner imagery by National Remote Sensing Centre, Indian Space Research Organisation. Trend analysis was done using a linear regression model in different major forest types. There was a positive trend in NPP in all forest types studied. Statistically significant (p-value < 0.05) highest trend was observed in the thorn forest (+ 1.75 g C m-2 yr-1). Increase in forest greenness indicates warming. The change in forest productivity is one of the fingerprints of climate variability.